Pengaruh Implementasi Kebijakan Dan Mutu Pelayanan Terhadap Kepercayaan Masyarakat Dalam Pembuatan E-KTP Pada Dukcapil Kabupaten Bombana - Syahruddin Syahruddin; Aenal Fuad Adam; Syahrabudin Husein Enala; Frederikus Antonius Mana; Muhammad Novan Prasetya (Musamus Journal of Public Administration, 2023)
The problem of this research revolves around, the Influence of Implementation of Service Policies and Quality on Community Trust in Making Electronic KTP at Bombana Regency Population and Civil Registration Office. This study uses a quantitative approach with a description method. Data collected through questionnaires, processed with computers through Excel and SPSS programs, with regression equation formulas, then interpreted analyzed and described in accordance with the research objectives by using a sample of all employees in the district population and civil registration departement of Bombana. From the results of the regression linearity research and data alasysis obtainedfrom the tree hypoteses it turns out that the linear regression population, because the F count is signifikan at alpha =0,05. And the results of the study indicate that all three proposed workyng hypotesis are entirely accepted, this is data by obtaining positive regression coefficients, so that the implementation of the policy of making electronic ID Cards of service quality both separately and in integrated manner affects the trust of the public.To increase public trust better si that it will result in achieving the terget of making electronic ID Cards at the maximum population and civil registration departement of bombana regency, policy implementation and service quality is needed because if the policy implementation is effective and the service quality is good, public trust will tend to increase,conversely if the implementationof policies and service quality is lacking and ineffective then public trust will tend to decrease